Bipolar Dislocation of the First Metatarsal with Associated Lisfranc Injury: A Case Report and Literature Review - Amrane, Hemza; Boussaha, Toufik; Hasrouri, Ilies; Boukhentiche, Abdallah; Mekideche, Besma; Boudjouref, Nouar; Benmayouf, Nazim; Derdous, Chaouki; Khernane, Nacer (Scripta Medica, 2025)
Bipolar dislocation of the first metatarsal ("floating first metatarsal") is an exceptionally rare injury resulting from high-energy trauma, characterised by simultaneous dislocation at both the tarsometatarsal (Lisfranc) and metatarsophalangeal (MTP) joints. Despite the well-documented nature of Lisfranc injuries, isolated bipolar dislocations remain extraordinarily rare, with fewer than 25 cases reported in the literature. This study presents a case of bipolar dislocation with an associated Lisfranc fracture-dislocation, highlighting diagnostic challenges, surgical management and functional outcomes. A 32-year-old woman presented after a fall from a height with a severe deformation of the forefoot and complete functional impairment. Imaging revealed: a bipolar dislocation of the first metatarsal (Lisfranc and MTP joints), a Lisfranc fracture-dislocation type B2 according to Myerson, A spiral fracture of the second metatarsal Emergency surgical treatment included: open reduction via dorsal approach; double pin fixation (M1-M2 and M2-cuneiform); ligament repair. The postoperative protocol included 6 weeks of immobilisation without weight bearing followed by progressive rehabilitation. At 12-month follow-up: AOFAS score improved from 0 to 86/100; MTP range of motion: 45° dorsiflexion (20° plantarflexion); radiographic consolidation with preserved alignment; no instability or arthritic changes observed. This case demonstrates that anatomic reduction with dual pinning fixation yields excellent functional outcomes for this rare injury pattern. Early diagnosis (aided by the identified "double discontinuity" radiological sign) and strict adherence to postoperative protocols are critical for optimal recovery. Long-term surveillance remains essential to monitor for post-traumatic sequelae.